2017
DOI: 10.1007/s00381-017-3596-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for refractory temporal lobe epilepsy: a systematic review and meta-analysis with an emphasis on alleviation of seizure frequency outcome

Abstract: DBS is an effective therapeutic modality for intractable TLE, particularly in patients with lateralized EEG abnormalities and in patients treated on the ictal side. This meta-analysis provides evidence-based information for determining DBS suitability in presurgical counseling and for explaining seizure outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…During the first survey round, no consensus was achieved on the parameters that could improve ANT-DBS therapy outcome, including [42] PATIENTS PREDICTORS Age at seizure onset [42] Age at seizure onset [26] -Age at the time of ANT-DBS implantation [26,42] -Disease duration from the age of seizure onset to age at the time of ANT-DBS [26,42] Temporal lobe epilepsy [17,18,43] Seizure aetiology [26] Sex [42] Normal MRI without structural abnormality [43] Normal MRI without structural abnormality [42] Partial seizures or secondarily generalized seizures [42] Less impaired patients [21] Lateralized EEG abnormalities (TLE) [42] Prior surgery / VNS treatment [17,18] Note: studies listed in Table 1 included different numbers of patients, thus a direct comparison might be inaccurate. different electrode target positions, micro-electrode guided implantation, awake implantation, and ictal side treatment.…”
Section: Patient Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first survey round, no consensus was achieved on the parameters that could improve ANT-DBS therapy outcome, including [42] PATIENTS PREDICTORS Age at seizure onset [42] Age at seizure onset [26] -Age at the time of ANT-DBS implantation [26,42] -Disease duration from the age of seizure onset to age at the time of ANT-DBS [26,42] Temporal lobe epilepsy [17,18,43] Seizure aetiology [26] Sex [42] Normal MRI without structural abnormality [43] Normal MRI without structural abnormality [42] Partial seizures or secondarily generalized seizures [42] Less impaired patients [21] Lateralized EEG abnormalities (TLE) [42] Prior surgery / VNS treatment [17,18] Note: studies listed in Table 1 included different numbers of patients, thus a direct comparison might be inaccurate. different electrode target positions, micro-electrode guided implantation, awake implantation, and ictal side treatment.…”
Section: Patient Managementmentioning
confidence: 99%
“…Although ANT-DBS treatment is a safe and effective treatment for DRE patients, predictors for positive outcome are still scarce. Previous reports suggested that defined electrode location within the ANT [28,31], temporal epilepsy syndromes [17,18,29,42,43] especially with later age at disease onset, lateralized EEG abnormalities, and ictal side treatment [42], patients with limited impairment [21], as well as positive performance in executive function tests [45] might be associated with a favourable outcome. Accordingly, the EP members approved ANT-DBS treatment in DRE patients with TLE who are no candidates for resective surgery and those who did not sufficiently benefit from resection/VNS therapy.…”
Section: Patient Selectionmentioning
confidence: 99%
“…There is a lack of meta-analyses and reviews specifically evaluating the possible nuclei to be stimulated. [9][10][11][12] A recent study assessed the procedure on the ANT, on the centromedian thalamic nucleus (CM), or on the hippocampus. 10 The authors reported a mean seizure reduction of 60.8% among the patients, but they did not separate the studied population into two different groups based on their follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 To address this problem, several nondestructive neuromodulation strategies have been developed to provide a safe and reversible treatment option for medically refractory and unresectable MTLE. [6][7][8] Currently, there are three clinically approved electrical stimulation treatment options: vagus nerve stimulation (VNS), responsive neurostimulation (RNS; United States only), and deep brain stimulation of the anterior nucleus of the thalamus (ANT-DBS), all of which target epileptic networks within the brain. [9][10][11] VNS has a well-established role in epilepsy therapy, and in general leads to approximately 50% reduction in seizure frequency in nearly 50% of patients at 12 months.…”
Section: Introductionmentioning
confidence: 99%